Pengaruh Keterlibatan Orang Tua Terhadap Motivasi Belajar Siswa Kelas IV Sekolah Dasar Masa Pandemi Covid-19 - Risal M. Merentek (Peneliti.net, 2022)
This study aims to determine whether there is an influence of parental participation on the learning motivation of fourth-grade students at GMIM Ranolambot Elementary School and to determine how much influence parent participation has on the learning motivation of fourth-grade elementary school students. The type of research used is a quantitative approach with survey methods, in which research is carried out using questionnaires as a research tool carried out on large and small populations, but the data studied is data from samples taken from these populations so that relative occurrences and distributions are found. , and the relationship between variables, sociological and psychological. The data collection was carried out by interviews, questionnaires, observation, and a combination of the three. The instrument used is a questionnaire containing closed statements. so that alternative answers to respondents have been provided by researchers. The questionnaire that will be used in data collection consists of two questionnaires, namely the parent participation questionnaire and the learning motivation questionnaire for grade IV elementary school students. Based on the t value, it is known that the tcount value is 5.860 > ttable 2.306 with an R contribution/contribution of 0.811 or 81.1%, which means that there is an influence of parental participation on the learning motivation of fourth-grade elementary school students, with an effect size of 81.1% on learning motivation student. Based on the results of the research and discussion, it can be concluded that there is a significant influence between parents' attention on the learning motivation of fourth-grade elementary school students.